Speech evoked auditory brainstem responses in children with learning disability - ., Sachin; Munjal, Sanjay; Kohli, Adarsh; Panda, Naresh; Arya, Shantanu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Learning disabilities are characterized by significant impairments in acquisition of reading, spelling or arithmetic skills. A growing number of studies have used speech sounds to assess auditory processing to linguistic elements in children with learning disability. The present study seeks to report whether speech evoked Auditory Brainstem Responses can be used as a biological marker of deficient sound encoding in children with learning disability. The study aims to establish relationship between click evoked auditory brainstem responses (ABR) and speech evoked ABR in children with learning disability; to report whether speech evoked auditory brainstem responses can be used as a biological marker of deficient sound encoding in children with learning disability. Methods: Pure tone audiometry, immitance audiometery, click and speech evoked brainstem responses were obtained in 25 children diagnosed with learning disability and the data was compared with the responses in the control group. Results: Statistical differences were seen in speech recognition threshold, speech discrimination scores, latencies and amplitude of speech evoked auditory brainstem responses between control and study group. This poor representation of significant components of speech sounds in children with learning disability could be due to synaptic efficacy distortion and poor synaptic transmission. Other reasons may be activation of fewer auditory nerve fibres in the auditory brainstem in response to speech stimulus. Conclusions: The speech evoked auditory brainstem responses can serve as an efficient tool in identifying underlying auditory processing difficulties in children with learning disability and can help in early intervention.